A study on determinants of profitability of MCIS Safety Glass Sdn Bhd / Siti Nurbasrah Nazran - Nazran, Siti Nurbasrah (2011)
This paper looks at financial statement variable that likely have an impact on firm profitability. Researcher collect firm financial data from recent years and test for factors affecting company’s Return on Assets. Researcher concentrate on two factors which are internal factors and external factors. Researcher find evidence that firm’s debt to equity and liquidity are all significant in determining ROA. Furthermore, Researcher found evidence that inflation rate and interest rate from external factors were also relatively significant.